Spatial and temporal distribution of false codling moth across landscapes in the Citrusdal area (Western Cape Province, South Africa). - Stotter, Robert L. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Conservation Ecology and Entomology)--University of Stellenbosch, 2009.